Dietary effects of Cissus populnea and Securidaca longepedunculata aqeous leave extracts on reproductive, haematological and biochemical parameters of Clarias gariepinus (Burchell, 1822) brood stocks - Ademola Zaid Aderolu; Muyideen Owonire Lawal; Luke Ikechukwu Okoronkwo; Funmileyi Olubajo Awobajo; Faith Iyanuoluwa Jesuniyi (Syiah Kuala University, 2017)
Sixty Clarias gariepinus broodstocks were fed with varying inclusion levels of Cissus populnea (CP) and Securidaca longepedunculata (SL). Diet 1 (control, 0 ml plant extract), Diet 2(0.5ml/kg CP), Diet 3 (1.0ml/kg CP), Diet 4 (0.5ml/kg SL), Diet 5 (1.0ml/kg SL), Diet 6 (0.5ml/kg CP + 0.5ml/kg SL) were fed for 90days to evaluate gametes quality, haematological and biochemical parameters. The results of haematocrit and red blood cell of treated groups were relatively similar to the control. The white blood cell and haemoglobin values were lower than the control group while the mean corpuscular volume, mean corpuscular haemoglobin were significantly difference across treatments however; an elevated glucose level was recorded in the treated groups. Also, the mean platelet volume and platelet distribution width were relatively similar across treatments. The serum testosterone, progesterone and estrogen were found to be higher in fish fed diet 2 (0.5ml/kg CP). C. populnea at 0.5ml/kg significantly (p0.05) improved eggs weight, fecundity, gonadosomatic index, % fertilization and hatchability. Male brood stocks fed on diet 2 (0.5ml/kg CP) recorded the highest values for sperm motility (56.67 ± 0.33%), milt count and volume (820.33 ± 0.33×106/ml and 1.80 ± 0.05ml respectively) across all groups. Similarly, diet 2 (0.5ml/kg CP) had the highest values for eggs weight (283.7±102.4g), fecundity (168,286 ± 57157), gonadosomatic index (32.59 ± 2.72), fertilization (62 ± 20.4%) and hatchability (62.92 ± 19.75%).The dietary supplementation of 0.5 ml/kg C. populnea extract highly enhanced the reproductive profiles of male and female C. gariepinus brood stocks.